Serum levels of TSP‐1, NF‐κB and TGF‐β1 in polycystic ovarian syndrome (PCOS) patients in northern China suggest PCOS is associated with chronic inflammation. (19th October 2015) - Liu, Meimei; Gao, Jiayin; Zhang, Yanhua; Li, Peiling; Wang, Hongli; Ren, Xiaopang; Li, Changmin
Summary: Objective: The objective of this study was to determine the levels of thrombospondin‐1 (TSP‐1), transforming growth factor‐β1 (TGF‐β1) and nuclear factor kappaβ (NF‐κβ) in polycystic ovarian syndrome (PCOS) patients with and without insulin resistance and after treatment with cyproterone acetate/ethinyloestradiol with or without concomitant metformin. Design: Prospective. Patients: Patients with PCOS and healthy women were recruited. Patients were subdivided into obese and nonobese based on body mass index. Patients with PCOS were also grouped according to homoeostasis model assessment‐insulin resistance (HOMA‐IR) ≥2·69 or <2·69, and by PCOS phenotype. Patients with PCOS‐IR were treated with a 6‐month course of cyproterone acetate/ethinyloestradiol with or without concomitant metformin. Measurements: Inflammatory markers were examined at baseline, and after 6 months of treatment. Results: A total of 445 women with PCOS (mean age 25·9 ± 2·7 years; 298 obese, 147 nonobese) and 213 normal controls (mean age 24·9 ± 3·0 years) were included. Regardless of obesity status, testosterone, free androgen index (FAI), luteinizing hormone/follicle‐stimulating hormone (LH/FSH) ratio, HOMA‐IR, TSP‐1 and NF‐κB in the PCOS groups were significantly higher than in the control group, whereas TSP‐1 was lower in the PCOS groups (all, P < 0·05). Patients with PCOS without IR had lower TSP‐1 levels than control patients ( P < 0·05). Treatment with cyproterone acetate/ethinyloestradiol with addition of metformin reduced the level of NF‐κB, TGF‐β1 and HOMA‐IR and increased the level of TSP‐1. Conclusions: These results support the association between PCOS and chronic inflammation.